The demographic features and outcome indicators of the Barbados HIV Pre-exposure Prophylaxis Program, 2018-2019 - Anton Best; Nastassia Rambarran (Pan American Health Organization, 2021)
Objectives. To assess the demographics, risk profiles and outcome indicators of one of the few government-supported programs on pre-exposure prophylaxis (PrEP) in the English-speaking Caribbean. Methods. Chart review of all persons enrolled into the national PrEP Program from its inception on March 1st 2018 to November 30th 2019, with a descriptive summary analysis of the data extracted. Results. Of the 134 persons enrolled into the program most identified as men who have sex with men (67.9%), followed by men who have sex with men and women (14.9%); there were 20 persons, mostly men (85%), in sero-discordant relationships. PrEP uptake was 96%; however, the continuation rate (continuing for three consecutive months after initiation) was 61.5%. Continuation status for many could not be ascertained due to loss-to-follow-up. PrEP-associated toxicity prevalence was 2.3%, although side-effects occurred in 52% (mostly gastrointestinal). HIV positivity during the study period was 1.5%. Conclusion. Uptake of Barbados' national PrEP Program is excellent but fairly low continuation rates and the HIV positivity rate indicate the need for improved pre-ART initiation education and follow-up processes. Service utilisation is mainly by men who have sex with men, and provision expansion to other civil society partners and private practitioners, as well as increased public awareness could increase access by other high-risk groups.